ESTIMATION OF CONTAMINATION WITH SOME METALLIC ELEMENTS IN CANNED PROCESSED MEAT PRODUCTS AVAILABLE IN LOCAL MARKETS. - Enas Najm Abdullah, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted to estimate the contamination with some heavy metals (lead, iron, copper, tin, and cadmium) in samples of canned processed meat available in the local markets. A sample were collected from three regions at Baghdad (Al-jamaa district S1, Al-Amel district S2 ,Al-Bayaa S3) with five samples, which included canned beef sausage, canned beef luncheon meat, and canned beef minced meat, which represented (45) samples as a total number. the atomic absorption spectrometer was used to estimate the contamination . The study results showed the presence of chemical contamination with heavy elements in concentrations higher than the permissible concentrations In most of the samples under study It has exceeded the permissible limits in the Iraqi standard, and thus it is not suitable for human consumption because it does not conform to the Iraqi standard, by exceeding the limits of concentrations of heavy elements from the limits allowed by the World Health Organization (WHO) and the World Food and Agriculture Organization (FAO) in the United Nations. The highest concentration Each of lead, iron and cadmium in beef sausage samples in treatment S3 (1.451, 2.342, 1.681) p.p.m compared to S2, which amounted to (0.684, 2.1131.380) p.p.m, respectively, and the lowest concentration of S1, which amounted to (0.068, 1.188, 1.07) p.p.m, respectively. The results also showed that the ratio of the copper and tin elements in most samples is within the permissible limits of the Iraqi standard.